Nilai-Nilai Kearifan Lokal dalam Cerita Rakyat Pasar Tambak Kumandang - Nasirudin al mustofa; Ali Imran Al Ma’ruf; Markhamah Markhamah (Jentera: Jurnal Kajian Sastra, 2024)
Researchers wish to conduct a study related to local wisdom values in the folklore Tambak Kumandang Market using literary anthropology studies. This research uses a qualitative description method. The strategy used is a single case study with only a focus on one criterion or target. The form of data in this research is words, sentences and discourse. Furthermore, this research uses primary and secondary data sources. This research data collection was carried out using various steps, namely observation, in-depth interviews, recording, noting and document analysis. Then this research uses data validation techniques in the form of triangulation and informant review. There are two triangulations used, namely data source and method triangulation. This research data analysis technique uses an interactive model created by Miles and Huberman. After analysis and discussion, it was concluded that there are seven local wisdoms in the folklore of Tambak Kumandang Market, namely: 1) language system number 4, 2) knowledge system number 10, 3) social organization system number 6, 4) economic system number 10. 3, 5) systems of living equipment and technology number 5, 6) religious systems number 9, and 7) art systems number 3.